Modeling of the Compaction Response of Jute Fabrics in Liquid Composite Molding Processes - Francucci, Gaston Martin (2012)
In this work, the experimental data of the compaction behavior of jute woven fabrics obtained in a previous work were modeled. A brief description of the current theoretical models found in literature is presented. It was concluded that these theoretical models cannot be used on natural fiber fabrics due to the vast differences in fiber structure and fibers assembly among natural and synthetic fibers. Therefore, two empirical models commonly seen in literature were used to fit the experimental data: the power law and the exponential function. In addition, a novel model was proposed, which represented much better the compaction behavior of the fabrics. The stress relaxation was also modeled using three empirical models: a power law, a first-order exponential function, and a second-order exponential function. The two-parameter power law model fitted the relaxation curve as well as the five-parameter exponential function. On the other hand, the first-order exponential function could not represent properly the relaxation stage.